ANALISIS KINERJA MODIFIKASI ALAT PENGUKUR DAN PEMBATAS SATU PHASE DIPELANGGAN YANG MENYEBABKAN SUSUT NONTEKNIS DI PT.PLN ULP MEULABOH - Dalimunthe, Muhammad Erpandi (Jurnal Informatika dan Teknik Elektro Terapan, 2024)
Misuse of electricity by customers is the cause of non-technical losses. Non-technical losses result in losses to the state, where PLN as the party that distributes electricity unknowingly loses its main commodity without any reciprocity in the form of payment. The form of misuse that is most often found by customers is in the form of modifications to the Measuring and Limiting Equipment (APP). It is important to know the variations in One Phase APP Modifications made by customers because they can be used as a reference to increase the success of PLN's P2TL program to reduce non-technical losses. To find variations in these modifications, it is necessary to analyze each result of misuse by customers and also categorize them so that they are easy to classify. There are four types of abuse, each month the highest violations are Classes I and III, although the percentage decreases in the following months, down to 53% from the beginning of the month when it reached 80%, the losses received by PLN due to this violation are in the RP range. 291,166,223.00 Thus, analysis of this modification variation can improve the results of the P2TL Program in order to reduce losses to PLN.